Ação civil pública: a tutela dos direitos difusos, coletivos e individuais homogêneos na esfera trabalhista - Valente, Tarcisio Regis (2007)
The changes observed on modern society has created the massive phenomenon, going through the strictly economical area to reach behaviours and social relationships, projecting, thus, the "metaindividual" interests against mainly individual conceptions regulated by the Civil Process Code. To satisfy these collective conception interests, Brazilian legislator has made specific laws in a way to make them possible, creating new "tools" to the process, that, besides individual guarantees, algo protect collective approach interests, democratizing the access to justice and giving them effectiveness, by means of public civil action or a collective action simply. The perfect integration between Lei n. 7.347/85 (Public Civil Action Law) and Lei n. 8.078/90 (Consumer Rights Code), as well as other casualty laws, has produced in our judicial procceding a truly collective civil process, able to resolve conflicts of collective interests, legally defined as "spred", collective and individual homogeneous. If these interests turn up in employment relations, the Unions and the Public Ministry of Labor are legally legitimate to make use of public civil action which is going to be judged by the Justice of Labor, the one that is able to resolve alI the conflicts between employees and employers